2017
DOI: 10.1007/s00726-017-2442-1
|View full text |Cite
|
Sign up to set email alerts
|

Dityrosine administration induces dysfunction of insulin secretion accompanied by diminished thyroid hormones T3 function in pancreas of mice

Abstract: Oxidized tyrosine products are commonly found in food with high protein content and have been demonstrated to cause damage of liver and kidney in our previous studies. Dityrosine (Dityr) is a typical oxidized tyrosine product. Due to its structural homology with thyroid hormones T3, we assumed that one of the endocrine systems most likely considered in connection with its disruption by Dityr may be the T3 action. T3 plays important roles in insulin synthesis, and thyroid hormone resistance (RTH) is associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…As Estévez and Luna reviewed, protein oxidation during digestion may be related to the onset and/or development of various chronic diseases. For example, oxidation products of lysine and tyrosine have been shown to alter glucose homeostasis and insulin secretion . Additional studies are however necessary to truly understand the (patho)physiological effects of PCC formed during the gastrointestinal digestion of foods.…”
Section: Resultsmentioning
confidence: 99%
“…As Estévez and Luna reviewed, protein oxidation during digestion may be related to the onset and/or development of various chronic diseases. For example, oxidation products of lysine and tyrosine have been shown to alter glucose homeostasis and insulin secretion . Additional studies are however necessary to truly understand the (patho)physiological effects of PCC formed during the gastrointestinal digestion of foods.…”
Section: Resultsmentioning
confidence: 99%
“…Li, Mo, Le, and Shi () found around 0.5 mg dityrosine per kg of protein in caseins oxidized in vitro. However, in subsequent studies, the same authors also found pathological effects lowering the dose of dityrosine to 320 μg/kg bw/day (Ding, Li et al., ). Using this dose, the authors hypothesized whether dityrosine could affect endocrine functions via the disruption of the T3 thyroid hormone owing to their structural homology.…”
Section: Pathogenesis Of Dietary Protein Oxidation: Recent Advancesmentioning
confidence: 91%
“…The intestinal uptake of specific protein oxidation products after oral administration, and the subsequent organic accumulation proves the bioavailability and bioactivity of these species which seem to have certain tropism for target tissues. This is the case of protein carbonyls for the intestinal epithelium (Keshavarzian et al., ), the α‐amino adipic acid for pancreas (Wang et al., ), and oxidized tyrosines for pancreas, kidney and liver (Ding, Cheng et al., ; Ding, Li et al., ; Ding, Tang et al., ; Yang, Zhang et al., , Yang, Yan et al., ). Finally, it is worth noting that the elevation of protein oxidation markers in blood and tissues may not only be caused by the intake of such species.…”
Section: Dietary Protein Oxidation and Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Yang et al ., the intake of dityrosines impairs assorted systemic metabolic processes, facilitates fat accumulation in liver, induces hepatic and renal injury, affects the gut microbiota function, and increases the risk factor for cardiovascular diseases. Ding et al . observed that dietary dityrosines disrupt pancreas functionality, leading to glucose metabolism disorder.…”
Section: Resultsmentioning
confidence: 99%